Detection of the 35S promoter by real-time PCR as a transgenicity indicator in food and Gossypium sp. - Oviedo-Bolaños, Karen; García-González, Jaime; Solano-González, Stefany; Martínez-Debat, Claudio; Sancho-Blanco, Carolina; Umaña-Castro, Rodolfo (Agronomía Mesoamericana, 2020)
Introduction. Genetically modified crops (GMC) are of particular interest due to their impact on the global economy. Therefore, as a general concern, many countries have established some regulations in regards to genetically modified organisms (GMOs). In Costa Rica, the cultivation of GMOs has been practiced since 1991; however, there´s a lack of studies that monitor the execution and compliance with the biosafety regulations. Objective. The objective of the present study was to identify the presence or absence of transgenicity in processed foods for human and animal consumption, as well as in cotton seeds. Material and methods. The real-time PCR technique was used to target the 35S promoter sequence, derived from the cauliflower mosaic virus (CaMV), as a marker to detect the presence of transgenes in processed foods for human and animal consumption as well as in wild or cultivated cotton seeds collected nearby a GM cotton farm in May 2017. Results. In the analyzed samples there was a high incidence of an 82 bp fragment, corresponding to the 35S promoter sequence, being absent only in organic corn crops and their derivatives (tortillas, corn powder). Results suggest the presence of GMO traces in the Costa Rican food market, additionally it reveals the urgency of implementing adequate labeling for food traceability. Furthermore, the presence of transgenic cotton in the vicinity of a GM cotton farm was identified, suggesting the relevance of surveillance in aspects of biosafety and genetic manipulation of crops. Conclusion. The presence of traces for GMOs in Costa Rican processed food, demonstrates the importance of continuing this monitoring to provide enough elements for a critic discussion about food traceability and potential transgene flow into wild plant material.